ANALISIS PENGELOLAAN ARSIP DI UNIT KEARSIPAN II FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS SEBELAS MARET SURAKARTA - Indah Rahmatul Ummah (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2018)
This research is Archives Management In UK II FKIP UNS Surakarta. This research position is to find : the management of inactive archives, detention of the archives management, the efforts that should be done to overcome obstacles. This research is a qualitative descriptive study. The results show that the management of inactive archives includes: management of incoming and outgoing mails, archival storage with university’s classification system, borrowing, rediscovery, shortening of archives by JRA, shortening by removal of inactive archives from work units to UK II, destruction of archives that have no use value, submission of static archives to the UNS Archival Unit, archive maintenance and archive custody. The obstacles faced are the infrastructure and facilities has not yet fulfilled the standard of archive management, human resource limitations, lack of security, maintenance of poorly watched archive, and the absence of some of archive. Efforts that should be done to overcome obstacles are the submission of infrastructure and facilities, the utilization of employees and students who are doing the internship, simple maintenance and securing with archival scan, rediscovery by keep track of the start.